2021
DOI: 10.3389/fimmu.2021.654406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Gain- and Loss-of-Function Germline Mutations in STAT1: A Systematic Review

Abstract: Background: Germline mutations in signal transducer and activator of transcription 1 (STAT1), which lead to primary immunodeficiency, are classified as defects in intrinsic and innate immunity. To date, no comprehensive overview comparing GOF with LOF in early-onset immunodeficiency has been compiled.Objective: To collect and systematically review all studies reporting STAT1 GOF and LOF cases, and to describe the clinical, diagnostic, molecular, and therapeutic characteristics of all the conditions.Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(123 citation statements)
references
References 43 publications
5
114
0
Order By: Relevance
“…The patient in our study presented with only recurrent and persistent infections of the skin, nails and mucous membranes, occurring since birth, and he did not have invasive candidiasis or autoimmune endocrine disease, which could be explained by his normal hormone levels. From the literature, we know that although Candida albicans is the most common species isolated from CMC patients, invasive species can also be found, including invasive Cryptococcus spp., Pneumocystis jirovecii, invasive Aspergillus spp., and invasive T. marneffei (8,15). However, this patient did not suffer from invasive fungal infections and only had isolated instance of CMC before this hospitalization.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The patient in our study presented with only recurrent and persistent infections of the skin, nails and mucous membranes, occurring since birth, and he did not have invasive candidiasis or autoimmune endocrine disease, which could be explained by his normal hormone levels. From the literature, we know that although Candida albicans is the most common species isolated from CMC patients, invasive species can also be found, including invasive Cryptococcus spp., Pneumocystis jirovecii, invasive Aspergillus spp., and invasive T. marneffei (8,15). However, this patient did not suffer from invasive fungal infections and only had isolated instance of CMC before this hospitalization.…”
Section: Discussionmentioning
confidence: 84%
“…From the literature, we know that although Candida albicans is the most common species isolated from CMC patients, invasive species can also be found, including invasive Cryptococcus spp. , Pneumocystis jirovecii, invasive Aspergillus spp., and invasive T. marneffei ( 8 , 15 ). However, this patient did not suffer from invasive fungal infections and only had isolated instance of CMC before this hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…It also causes autoimmune endocrinopathies, such as thyroiditis and T1DM. In a meta-analysis, autoimmune thyroiditis and T1DM were observed in 23.0% and 5% of STAT1 GOF patients, respectively ( 54 ). On the other hand, recent in vitro and in vivo studies have demonstrated an essential role for STAT1 in islet cell death.…”
Section: Pathophysiology Of Endocrinopathy In Ieimentioning
confidence: 99%
“…Over the past 15 years, monogenic disorders in the STAT1 gene have been described including biallelic loss of function (LOF) causing a profound combined immunodeficiency (CID) ( 5 7 ), a dominant negative LOF resulting in Mendelian Susceptibility to Mycobacterial Disease (MSMD) ( 8 , 9 ), and an autosomal dominant gain-of-function (GOF) ( 10 , 11 ). To date, over 400 cases of STAT1 GOF have been reported, making it the most common genetic cause identified in patients with chronic mucocutaneous Candidiasis (CMCC) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%